Populist Rhetoric in Electoral Political Space of Modern Russia: Regional Aspect - Efanova Elena Vladimirovna (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 4. Istoriâ, Regionovedenie, Meždunarodnye Otnošeniâ, 2015)
The article presents the analysis of regional features of populist rhetoric realization as the basis of electorate mobilization. The motivational characteristics of electoral preferences are established, the strategy of populist policy in the Russian Federation is determined. The populist rhetoric defines policy as moral and ethical fight between the people and oligarchy. In electoral political space of modern Russia populism is considered in a negative connotation, it has manipulative impact on public consciousness of Russians, it forms political expectations and electoral preferences. In the analysis of regional electoral process it is necessary to consider a phenomenon of patronclient relations being a factor of electoral preferences which ensures the platform for forming the relations of domination, supremacy and subordination. In Russian electoral political space there are patriarchal, traditional, client-oriented, protest and marginal types of electoral behavior. The patriarchal (Republics of the North Caucasus, Siberia) and traditional (Saint Petersburg, Belgorod region) types create the conditions for populism use as it is easier for populists to win electorate of the senior generation which are committed to traditional values and customs.